Multi-impurity-element-resistant and poisoning CO oxidation-resistant catalyst as well as preparation method and application thereof
By loading active components such as Pt, Pd, Ru and additive elements such as Sn, V, and Mo on the surface of TiO2 support, a catalyst with high-efficiency CO oxidation activity and anti-toxicity ability of multiple impurities was constructed, which solved the problem of poisoning of existing catalysts in a variety of impurities environments and achieved efficient purification of industrial CO waste gas.
Patent Information
- Application Number
- CN202411850017.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-29
AI Technical Summary
When using industrial waste gases, existing CO oxidation catalysts are prone to poisoning due to the existence of impurities and lose their catalytic activity, making it difficult to cope with the complex composition of multiple impurities.
A catalyst composed of TiO2 carrier and active component elements and additive elements supported on the surface are used. The active component elements are selected from Pt, Pd, Ru, and the additive elements are selected from Sn, V, Mo, Nb, Zr, Cr, and Mn. Through the interaction between the additive elements and the carrier, the charge redistribution of the catalyst surface and the selective adsorption of impurity elements are achieved to avoid the toxicity of the active components of noble metals.
This catalyst has excellent CO oxidation activity and resistance to poisoning resistance of various impurities. It is suitable for the purification of industrial CO waste gas of multiple impurities, and is especially suitable for the purification and treatment of steel sintered flue gas and industrial kiln exhaust gas.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to a catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation, and a preparation method and application thereof, belonging to the field of catalysts. Background Art
[0002] CO is highly toxic and relatively stable in nature, posing a serious threat to the ecological environment and people's life and health.
[0003] Catalytic combustion technology can oxidize CO into non-toxic CO2 in the presence of a catalyst, and has the advantages of simple equipment, high efficiency, wide application range, and thorough treatment. However, due to the complex composition of industrial waste gas, it often contains impurities such as sulfur, chlorine, phosphorus, selenium, and arsenic, which can cause the noble metal sites in the CO oxidation catalyst to be poisoned and lose catalytic activity. Therefore, improving the resistance of the catalyst to various impurities and solving the problem of catalytic poisoning are the key to realizing the application and promotion of catalytic combustion CO purification.
[0004] For a long time, the development of poisoning-resistant CO oxidation catalysts has often focused only on the impact of one or one type of impurity on the catalyst. For example, CN114669286A and CN114643065A respectively disclose methods for improving the sulfur resistance of CO oxidation catalysts, and CN118304885 and CN118217979A disclose methods for improving the resistance of CO oxidation catalysts to heavy elements such as selenium and arsenic. However, due to the complex composition of industrial waste gas, resistance to a single impurity is difficult to cope with the poisoning of multiple impurity elements under complex composition in practical applications. Summary of the invention
[0005] The present invention provides a CO oxidation catalyst which is resistant to poisoning by multiple impurity elements. The catalyst has excellent CO oxidation activity and anti-poisoning ability by multiple impurity elements.
[0006] According to one aspect of the present application, a catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation is provided, wherein the catalyst is composed of a TiO2 carrier and active component elements and auxiliary elements loaded on the surface of the TiO2 carrier;
[0007] The active component element is selected from at least one of Pt, Pd and Ru;
[0008] The auxiliary element is selected from at least one of Sn, V, Mo, Nb, Zr, Cr and Mn;
[0009] In the catalyst, the mass content of the active component element is 1-20wt%, and the mass content of the auxiliary element is 0.05-1.5wt%;
[0010] The crystal form of the TiO2 carrier is selected from at least one of anatase and rutile, and the size is less than 100nm, preferably P25;
[0011] The active component elements exist in the form of highly dispersed single atoms, clusters or nanoparticles in a high-valence state;
[0012] The auxiliary element is present in the form of an oxide.
[0013] The catalyst has excellent resistance to poisoning by sulfur, chlorine, phosphorus and selenium.
[0014] According to another aspect of the present application, a method for preparing the above-mentioned catalyst is provided, comprising the following steps:
[0015] The TiO2 carrier is immersed in an aqueous solution containing an additive, an active component precursor and an auxiliary agent precursor in equal volume, dried, calcined in an air atmosphere, immersed in a reducing agent for reduction, separated, and dried to obtain the catalyst.
[0016] The active component precursor is selected from at least one of the nitrates or hydrochlorides of Pt, Pd, and Ru;
[0017] The auxiliary agent precursor is selected from at least one of nitrates, oxalates, hydrochlorides or ammonium salts of Sn, V, Mo, Nb, Zr, Cr and Mn;
[0018] The additive is selected from at least one of ethanol, butanol, acetic acid, oxalic acid and tartaric acid.
[0019] The drying temperature is 80-150°C;
[0020] The drying time is 5 to 24 hours.
[0021] The calcination temperature is 400-600°C;
[0022] The calcination time is 2 to 5 hours.
[0023] The reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid, formic acid or sodium borohydride solution;
[0024] The immersion time is 10min to 24h;
[0025] The drying temperature is 80-150°C;
[0026] The drying time is 5 to 24 hours.
[0027] According to another aspect of the present application, there is provided an application of the above-mentioned catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation, which is used for purification of industrial CO waste gas containing multiple impurities.
[0028] According to another aspect of the present application, there is provided an application of the above-mentioned catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation, which is used for the purification of steel sintering flue gas and industrial kiln tail gas.
[0029] The catalyst provided by the present invention utilizes the interaction between the auxiliary element and the carrier to realize the redistribution of the charge on the catalyst surface, realizes the site-selective preferential adsorption of different impurity elements, and avoids the poisoning of the noble metal active components. The noble metal active components exist in the form of highly dispersed single atoms and clusters, presenting an electron-deficient state, which inhibits the irreversible adsorption of impurity elements at the active site, thereby improving the anti-poisoning performance. The catalyst of the present invention has efficient carbon monoxide catalytic oxidation activity, low operating temperature, good stability, excellent sulfur resistance, chlorine resistance, phosphorus resistance and selenium resistance, and is suitable for industrial carbon monoxide waste gas purification with multiple impurities, and is particularly suitable for the purification of steel sintering flue gas and industrial kiln tail gas. The catalyst preparation process is short, the operation is simple, the cost is low, and it is convenient for large-scale production.
[0030] The beneficial effects of this application include:
[0031] 1. The catalyst of the present invention constructs a large number of medium-strength acid sites by using additives in the form of oxides or mixed oxides on the surface of the TiO support, thereby effectively inhibiting the adsorption of acidic impurities on the catalyst surface.
[0032] 2. The auxiliary element mixed oxide of the present invention is composed in a certain proportion. On the one hand, the acid strength is adjusted by charge redistribution, and on the other hand, the site-selective preferential adsorption of different impurity elements is achieved to avoid poisoning of the noble metal active components.
[0033] 3. The noble metal active components in the present invention exist in the form of highly dispersed single atoms and clusters, presenting an electron-deficient state, which inhibits the irreversible adsorption of impurity elements at the active sites, thereby improving the anti-poisoning performance.
[0034] 4. The catalyst of the present invention has high CO oxidation activity, low operating temperature, good stability, and excellent anti-poisoning properties such as sulfur resistance, chlorine resistance, phosphorus resistance and selenium resistance. It is suitable for purification of industrial CO waste gas with many impurities, and is particularly suitable for purification of steel sintering flue gas and industrial kiln tail gas.
[0035] 5. The catalyst preparation process of the present invention is short, simple to operate, low in cost, and convenient for large-scale production. DETAILED DESCRIPTION
[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0037] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0038] Example 1
[0039] Immerse equal volumes of TiO2 P25 in a mixed solution of tin chloride, niobium oxalate, and chloroplatinic acid. The mass ratio of Sn:Pt:TiO2 is 3:0.5:100. Dry the obtained wet powder at 120°C for 12 hours. Calcinate the dried powder at 500°C in a muffle furnace under air for 3 hours. Immerse and reduce the calcined sample in a sodium borohydride reducing agent for 10 minutes. Separate the impregnated powder and dry it at 120°C for 12 hours.
[0040] Example 2
[0041] The impregnation solution is obtained by mixing a solution of 8% tartaric acid dissolved by stirring at 30°C and a solution of chloroplatinic acid dissolved by stirring at 50°C in 5% oxalic acid; an equal volume of TiO2 P25 is impregnated in the above mixed solution. Among them, the mass ratio of Nb:Pt:TiO2 is 3:1:100. The obtained wet powder is dried at 80°C for 12 hours. The dried powder is placed in a muffle furnace under air at 500°C for 3 hours. The calcined sample is placed in a sodium borohydride reducing agent for immersion reduction for 30 minutes. The impregnated powder is separated and dried at 100°C for 12 hours.
[0042] Example 3
[0043] A solution of zirconyl chloride dissolved in deionized water at 30°C and a solution of chloroplatinic acid dissolved in ethanol at 50°C are mixed to obtain an impregnation solution; an equal volume of TiO2 P25 is impregnated in the above mixed solution. Among them, the mass ratio of Zr:Pt:TiO2=3:0.2:100. The obtained wet powder is dried at 100°C for 12 hours. The dried powder is placed in a muffle furnace under air at 600°C for 2 hours. The calcined sample is placed in a sodium borohydride reducing agent for immersion reduction for 20 minutes. The impregnated powder is separated and dried at 100°C for 12 hours.
[0044] Example 4
[0045] The solution of ammonium heptamolybdate dissolved in 10% oxalic acid at 50°C and the solution of chloroplatinic acid dissolved in deionized water at 50°C were mixed to obtain an impregnation solution; an equal volume of TiO2 P25 was impregnated in the above mixed solution. Among them, the mass ratio of Mo:Pt:TiO2=5:1:100. The obtained wet powder was dried at 120°C for 12 hours. The dried powder was placed in a muffle furnace under air at 600°C for 2 hours. The calcined sample was placed in a sodium borohydride reducing agent for immersion reduction for 60 minutes. The impregnated powder was separated and dried at 120°C for 12 hours.
[0046] Example 5
[0047] The solution of tin chloride dissolved in deionized water at 30°C and niobium oxalate dissolved in 8% tartaric acid at 30°C and the solution of chloroplatinic acid dissolved in 5% oxalic acid at 50°C were mixed to obtain an impregnation solution; an equal volume of TiO2 P25 was impregnated in the above mixed solution. Among them, the mass ratio of Sn:Nb:Pt:TiO2=5:5:1:100. The obtained wet powder was dried at 120°C for 12 hours. The dried powder was placed in a muffle furnace under air at 600°C for 3 hours. The calcined sample was placed in a sodium borohydride reducing agent for immersion reduction for 60 minutes. The impregnated powder was separated and dried at 120°C for 12 hours.
[0048] Example 6
[0049] The solution of ammonium molybdate and niobium oxalate stirred at 30°C in deionized water, the solution of chloroplatinic acid stirred at 50°C in 5% oxalic acid, and the solution of palladium nitrate stirred at 50°C in 5% tartaric acid were mixed to obtain an impregnation solution; an equal volume of TiO2 P25 was impregnated in the above mixed solution. Among them, the mass ratio of Mo:Nb:Pd:Pt:TiO2=5:3:0.5:0.5:100. The obtained wet powder was dried at 120°C for 12 hours. The dried powder was placed in a muffle furnace under air and roasted at 600°C for 3 hours. The roasted sample was placed in a hydrazine hydrate reduction reagent for immersion reduction for 24 hours. The impregnated powder was separated and dried at 120°C for 12 hours.
[0050] Example 7
[0051] The solution of niobium oxalate stirred at 30°C in deionized water, the solution of chloroplatinic acid stirred at 30°C in 5% oxalic acid, and the solution of ruthenium trichloride stirred at 50°C in 5% tartaric acid were mixed to obtain an impregnation solution; an equal volume of TiO2 P25 was impregnated in the above mixed solution. Among them, the mass ratio of Nb:Ru:Pt:TiO2=5:0.5:0.5:100. The obtained wet powder was dried at 110°C for 12 hours. The dried powder was placed in a muffle furnace under air and roasted at 600°C for 3 hours. The roasted sample was placed in an ascorbic acid reducing agent for 90 minutes. The impregnated powder was separated and dried at 100°C for 12 hours.
[0052] Example 8
[0053] A solution of niobium oxalate stirred at 30°C in deionized water, a solution of tin chloride stirred at 30°C in deionized water, a solution of ammonium molybdate stirred at 30°C in deionized water, a solution of chloroplatinic acid stirred at 50°C in 5% oxalic acid, and a solution of palladium nitrate stirred at 50°C in 10% tartaric acid were mixed to obtain an impregnation solution; an equal volume of TiO2 P25 was impregnated in the above mixed solution. Among them, the mass ratio of Sn: Nb: Mo: Pd: Pt: TiO2 = 3: 3: 5: 0.3: 0.2: 100. The obtained wet powder was dried at 80°C for 12 hours. The dried powder was placed in a muffle furnace under air and roasted at 600°C for 2 hours. The roasted sample was placed in a sodium borohydride reducing agent for immersion reduction for 20 minutes. The impregnated powder was separated and dried at 120°C for 12 hours.
[0054] Comparative Example 1
[0055] The tin chloride-deionized water solution in Example 1 was removed, and other conditions remained unchanged. Compared with Example 3, this comparative example did not load the co-catalyst SnO2.
[0056] Comparative Example 2
[0057] The niobium oxalate-tartaric acid solution in Example 5 was removed, and other conditions remained unchanged. Compared with Example 3, this comparative example did not load the co-catalyst Nb2O5.
[0058] Comparative Example 3
[0059] The ammonium molybdate-deionized water solution in Example 6 was removed, and other conditions remained unchanged. Compared with Example 6, this comparative example did not load the co-catalyst MoO3.
[0060] The catalyst was subjected to a catalytic combustion experiment. The raw material was CO gas containing at least one of sulfur dioxide, hydrogen sulfide, vinyl chloride, phosphine, and selenium dioxide. The reaction was carried out at 250° C. for 10 hours. The conversion rate of impurities is shown in Table 1.
[0061] Table 1
[0062]
[0063]
[0064] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation, characterized in that: The catalyst is composed of a TiO2 carrier and active component elements and auxiliary elements loaded on the surface of the TiO2 carrier; The active component element is selected from at least one of Pt, Pd and Ru; The auxiliary element is selected from at least one of Sn, V, Mo, Nb, Zr, Cr and Mn; In the catalyst, the mass content of the active component element is 1-20wt%, and the mass content of the auxiliary element is 0.05-1.5wt%; The crystal form of the TiO2 carrier is selected from at least one of anatase and rutile; The active component elements exist in the form of highly dispersed single atoms, clusters or nanoparticles in a high-valence state; The auxiliary element is present in the form of an oxide.
2. A method for preparing the catalyst according to claim 1, characterized in that: The following steps are involved: The TiO2 carrier is immersed in an aqueous solution containing an additive, an active component precursor and an auxiliary agent precursor in equal volume, dried, calcined in an air atmosphere, immersed in a reducing agent for reduction, separated, and dried to obtain the catalyst.
3. The preparation method according to claim 2, The active component precursor is selected from at least one of the nitrates or hydrochlorides of Pt, Pd, and Ru; The auxiliary agent precursor is selected from at least one of nitrates, oxalates, hydrochlorides or ammonium salts of Sn, V, Mo, Nb, Zr, Cr and Mn; The additive is selected from at least one of ethanol, butanol, acetic acid, oxalic acid and tartaric acid.
4. The preparation method according to claim 2, The drying temperature is 80-150°C; The drying time is 5 to 24 hours.
5. The preparation method according to claim 2, The calcination temperature is 400-600°C; The calcination time is 2 to 5 hours.
6. The preparation method according to claim 2, The reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid, formic acid or sodium borohydride solution; The immersion time is 10 minutes to 24 hours; The drying temperature is 80-150°C; The drying time is 5 to 24 hours.
7. Use of the catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation according to claim 1, characterized in that: Used for purification of industrial CO waste gas containing various impurities.
8. Use of the catalyst resistant to multiple impurity elements and anti-poisoning CO oxidation according to claim 1, characterized in that: Used for purification of steel sintering flue gas and industrial kiln exhaust gas.
Citation Information
Patent Citations
Precious metal catalyst for catalytic oxidation of CO and preparation method thereof
CN114643065A
Platinum-based catalyst for CO oxidation and preparation method and application thereof
CN114669286A
Honeycomb type CO platinum oxide / palladium-based catalyst capable of resisting heavy metal poisoning as well as preparation method and application thereof
CN118217979A
Cited By
Sulfur-resistant moisture-proof CO oxidation regular-structure catalyst as well as preparation method and application thereof
CN121551025A
A sulfur-resistant and moisture-resistant CO oxidation regular structure catalyst, a preparation method and application thereof
CN121551025B